Characterization of a chitosan sample extracted from Brazilian shrimps and its application to obtain insoluble complexes with a commercial whey protein isolate - Daniele S. Bastos (2010)
The rheological behaviour of chitosan solutions in 250 mM acetate buffer was studied at different pHs (25 degrees C). The intrinsic viscosity decreased from similar to 17 dL/g to similar to 14 dL/g when the pH increased from 4.7 to 6.0. Concentrated solutions (0.5-3.0% w/w) exhibited a shear-thinning behaviour which increased with increasing chitosan concentration and decreasing pH. A good fitting of the experimental data to the Cross and Carreau flow models was obtained. The elasticity of the solutions decreased with increasing pH and decreasing chitosan concentration, as a consequence of increased chain flexibility. The interaction of chitosan with whey proteins (WPI) was studied by isothermal titration calorimetry (ITC) and turbidity measurements, at different pHs (3.0-6.0) and ionic strengths (100 and 250 mM). ITC results showed that electrostatics is the main driving force for chitosan: WPI interaction, as an increase in ionic strength lead to a smaller interaction. A pH and chitosan: WPI ratio dependence of aggregate formation was clearly observed by turbidimetry. At pH 3.0, there was no change in turbidity upon addition of chitosan, whereas at pH 4.0 and 6.0, the turbidity values varied with chitosan: WPI ratio and were smaller at 250 mM than those at 100 mM. The rheology of chitosan:WPI coacervates was studied in acetate buffer (100 and 250 mM), at pH 5.5, mixing ratios of 0.25:1 and 0.10:1. Time dependent flow behaviour, higher G' and G '' values and higher elasticity were observed for the coacervates, originating mainly from the electrostatic interactions between the protein and the polysaccharide chains.